2015
DOI: 10.1088/0957-4484/26/16/164003
|View full text |Cite
|
Sign up to set email alerts
|

Pd nanoparticles on ZnO-passivated porous carbon by atomic layer deposition: an effective electrochemical catalyst for Li-O2 battery

Abstract: Uniformly dispersed Pd nanoparticles on ZnO-passivated porous carbon were synthesized via an atomic layer deposition (ALD) technique, which was tested as a cathode material in a rechargeable Li-O2 battery, showing a highly active catalytic effect toward the electrochemical reactions-in particular, the oxygen evolution reaction. Transmission electron microscopy (TEM) showed discrete crystalline nanoparticles decorating the surface of the ZnO-passivated porous carbon support in which the size could be controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…The spectrum of the cathode at potential V 2 is very similar to the one of the electrolyte, as displayed in Figure S2, suggesting the formation of very small amounts of O-containing discharge products. 12 To quantify the different oxygen contributions, the spectrum is fitted with three components, as described in the following. First, we performed a three-component fit, using the spectra of Electrolyte, GDL, and lithium peroxide.…”
Section: Discharge Productsmentioning
confidence: 99%
“…The spectrum of the cathode at potential V 2 is very similar to the one of the electrolyte, as displayed in Figure S2, suggesting the formation of very small amounts of O-containing discharge products. 12 To quantify the different oxygen contributions, the spectrum is fitted with three components, as described in the following. First, we performed a three-component fit, using the spectra of Electrolyte, GDL, and lithium peroxide.…”
Section: Discharge Productsmentioning
confidence: 99%
“…[53,[101][102][103][104][105][106][107][108][109][110][111][112][113] However, these results have shown that it is impossible to maximize the electrochemical performance of a Li-O 2 battery without distinguishing the role of each catalyst for the ORR or OER. [53,[101][102][103][104][105][106][107][108][109][110][111][112][113] However, these results have shown that it is impossible to maximize the electrochemical performance of a Li-O 2 battery without distinguishing the role of each catalyst for the ORR or OER.…”
Section: Au-mos 2 Au-nico 2 O 4 Pd-co 3 O 4 Pd-mno 2 Pd-zno Andmentioning
confidence: 99%
“…The same group also tested ZnO instead of Al 2 O 3 as the passivation layer. The Pd grew faster on the ZnO layer, the overpotential on charge was almost zero, and the cyclability was also improved . The passivated cathode is well suited to study the catalytic mechanisms, and the metal oxide layer can improve the adhesion of catalysts on non‐carbon cathodes …”
Section: Lithium‐o2 Batteriesmentioning
confidence: 99%